Gut microbiota: a new frontier in understanding and protecting endangered plateau schizothorax fish - Pan, Hongbo; Liu, Haiping; Liu, Fei; Xie, Jianmei; Zhou, Yan; Zheng, Qize; Guo, Mingxiong (Frontiers in Microbiology, 2025)
IntroductionAgainst the backdrop of global biodiversity decline, the role of gut microbiota in endangered species conservation remains underexplored. Endemic fish species in Xizang are critical to plateau ecosystems, yet many face severe survival threats. This study investigates the association between gut microbiota composition and conservation status in five endemic fish species, including the nationally protected Oxygymnocypris stewarti, Schizothorax waltoni, and Schizothorax macropogon.MethodsUsing 16S rRNA sequencing, we systematically analyzed gut microbiota community structures across the five fish species. We compared microbial diversity, dominant bacterial phyla, and the influence of dietary habits on microbiota composition.ResultsDominant Bacterial Phyla: Fusobacteria, Proteobacteria, and Verrucomicrobia were common across species, while Tenericutes was uniquely dominant in endangered fish. Diversity Trends: Gut microbiota diversity followed the order: Ptychobarbus dipogon > S. waltoni > Schizothorax o-connori > S. macropogon > O. stewarti. Conservation Status Correlation: Species with higher endangerment levels exhibited significantly lower diversity: Least Concern (LC) > Near Threatened (NT) > Vulnerable (VU) > Endangered (EN). Dietary Influence: Phytophagous (PHY) fish had higher microbial diversity than omnivorous (OMN) and sarcophagous (SAR) fish, confirming diet as a key factor shaping gut microbiota.DiscussionThis study provides the first evidence linking gut microbiota composition to the conservation status of endemic Tibetan fish. The reduced microbial diversity in endangered species suggests potential microbiome-related health vulnerabilities. Additionally, dietary differences significantly influence microbiota structure, highlighting the need for habitat and dietary conservation strategies. These findings open new avenues for microbiome-based conservation approaches in endangered species management.